2012
DOI: 10.1038/modpathol.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-related markers in primary breast cancers and associated metastatic lesions

Abstract: It has been reported previously that: 1) normal breast epithelial cells that are CD24-/44+ express higher levels of stem/progenitor cell associated genes; 2) cancer cells that have undergone epithelial to mesenchymal transition display CD24-/44+ cell surface expression, a marker for breast cancer stem cells; 3) loss of E-cadherin is a preliminary step in epithelial to mesenchymal transition; and 4) vimentin is a marker of mesenchymal phenotype.We hypothesized that stem cell subpopulations would be more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
2
32
1
2
Order By: Relevance
“…Expression of vimentin was scored as follows: sections were scored from 0–3 where ‘0’ corresponds to lack of positive staining and ‘3’ represents the most intense staining. Scores were calculated as follows: average intensity of the stain (1–3) x average percentage of positive cells, as previously described [42]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of vimentin was scored as follows: sections were scored from 0–3 where ‘0’ corresponds to lack of positive staining and ‘3’ represents the most intense staining. Scores were calculated as follows: average intensity of the stain (1–3) x average percentage of positive cells, as previously described [42]. …”
Section: Methodsmentioning
confidence: 99%
“…CD24 (SN3b; Neomarkers) and CD44 (DF1485; Dako) expression was determined by double staining of tumor cells [42, 43]. …”
Section: Methodsmentioning
confidence: 99%
“…Tumors having a score of <100 were classified as E-cadherin low and those with a score ≥100 as E-cadherin high (Figure 1). This dichotomous cut-point was determined prior to genetic association analyses and was based on the observed distribution of the composite scores and supported by evidence in the literature (11, 12). …”
Section: Methodsmentioning
confidence: 99%
“…ALDH1+ phenotype was found to be associated with biological aggressiveness and poor outcomes of breast cancer 9, 16, 17. Notably, several reports indicated that CD44 + /CD24 - and ALDH1+ breast cancer cells were associated with TNBC subtype 18-21. CD133, a transmembrane glycoprotein, is a more recent BCSC marker identified to be correlated with prognosis in breast cancer.…”
Section: Introductionmentioning
confidence: 99%